(y-9)(y+9)=

Simple and best practice solution for (y-9)(y+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y-9)(y+9)= equation:


Simplifying
(y + -9)(y + 9) = 0

Reorder the terms:
(-9 + y)(y + 9) = 0

Reorder the terms:
(-9 + y)(9 + y) = 0

Multiply (-9 + y) * (9 + y)
(-9(9 + y) + y(9 + y)) = 0
((9 * -9 + y * -9) + y(9 + y)) = 0
((-81 + -9y) + y(9 + y)) = 0
(-81 + -9y + (9 * y + y * y)) = 0
(-81 + -9y + (9y + y2)) = 0

Combine like terms: -9y + 9y = 0
(-81 + 0 + y2) = 0
(-81 + y2) = 0

Solving
-81 + y2 = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '81' to each side of the equation.
-81 + 81 + y2 = 0 + 81

Combine like terms: -81 + 81 = 0
0 + y2 = 0 + 81
y2 = 0 + 81

Combine like terms: 0 + 81 = 81
y2 = 81

Simplifying
y2 = 81

Take the square root of each side:
y = {-9, 9}

See similar equations:

| (m+1)(m+1)= | | (a-5)(a+3)= | | 3r(r-5)-2r(3r-1)= | | -2a(3a^2-4a-1)= | | 5(2x-11)+17=52 | | 5x(4x-3)= | | 9x-10y=-7 | | 10(x-1)/2x+10x=5 | | (3p^2-q^2)-(4p^2-7q^2)= | | 8(x+3)+7=71 | | (4x^2+5x+1)-(3x^2-7x+4)= | | 29.25/0.36 | | (-3m^2+8n^2-6n)-[(8m^2-6m+2n)+(-8m^2)+4n^2]= | | 144+81= | | 5xn=4.5 | | 10(x-1)/2x+10 | | x=12+9 | | 45/18=9/x | | -4/5*(4*-34/4-1) | | (2)/(2x-5)=-2 | | -1/4x^2-x-8=0 | | -34/4 | | 2x+5x=-15x-6x | | x/6=12/8 | | 20/16=70/x | | 6/12=n/42 | | -4/5*(4a-1)=28 | | F(x)=-3x-8f(2) | | 5+4/x | | 3/x+2/5 | | 5/x-2/x | | 3/5(30x) |

Equations solver categories